2006
DOI: 10.1136/sti.2005.016774
|View full text |Cite
|
Sign up to set email alerts
|

Higher prevalence of human papillomavirus infection in migrant women from Latin America in Spain

Abstract: Objectives: To estimate prevalence and determinants of high risk (HR) human papillomavirus (HPV) by country of origin in women attending a family planning centre (FPC) . Conclusions: Prevalence of HR HPV is more than three times higher in Latin Americans than in Spaniards. Latin American women's HPV prevalence resembles more that of their countries of origin. It is essential that health service providers identify these women as a priority group in current cervical screening programmes T here is substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
19
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 10 publications
7
19
0
1
Order By: Relevance
“…High prevalence in CSW in Spain had been previously described, both in Spanish (44) and in migrant CSW individuals (9). The rate of oncogenic HPV prevalence in the general population for Spanish women agrees with data previously published in Spain (12,20) and are similar to those of others conducted in European countries, such as Italy, with rates of prevalence of between 6.6 and 7.1% (10,33).…”
Section: Discussionsupporting
confidence: 79%
“…High prevalence in CSW in Spain had been previously described, both in Spanish (44) and in migrant CSW individuals (9). The rate of oncogenic HPV prevalence in the general population for Spanish women agrees with data previously published in Spain (12,20) and are similar to those of others conducted in European countries, such as Italy, with rates of prevalence of between 6.6 and 7.1% (10,33).…”
Section: Discussionsupporting
confidence: 79%
“…14 This imbalance is further illustrated by recent literature indicating that women who had immigrated from Colombia to Spain were found to have a 27% prevalence of high-risk HPV types, compared to 8% of Spanish women living in the same region in Spain. 15 Furthermore, case-control studies of cervical cancer conducted in Brazil, Colombia, Paraguay and Peru have shown that HPV 16 and 18 are responsible for 65% of cervical squamous cell carcinoma and 84% of cervical adenocarcinomas in the countries listed above. 16,17 Genital warts constitute a separate, yet not unimportant issue for public health systems in Latin America.…”
mentioning
confidence: 99%
“…In this study, HPV-51 (7.8%), -52 (5.2%) and -66 (2.6%) were detected. These viral types appear to be common in the Spanish population [6,18,[35][36][37][38], and these HPV specific-genotypes were also detected in studies around the world. The proportions detected in these studies are diverse, being as high as 17.5%, 12.0%, and 8.1% respectively [35], while in other study [38] found similar rates to those of our study: 8.0%, 3.8%, and 7.1%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…In Spain, crude prevalence rates for HPV infection in small, specific populations or in limited geographical areas have been previously reported to range from 3% to 17% [17][18][19][20]. In a study to provide specific information for Spain in 1,043 histologically confirmed invasive cervical cancer cases from six regions, 904 of these cases (89.1%) were HPV DNA positive [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation